2021
DOI: 10.3390/jof7100843
|View full text |Cite
|
Sign up to set email alerts
|

P-Type ATPase Apt1 of the Fungal Pathogen Cryptococcus neoformans Is a Lipid Flippase of Broad Substrate Specificity

Abstract: Lipid flippases of the P4-ATPase family are ATP-driven transporters that translocate lipids from the exoplasmic to the cytosolic leaflet of biological membranes. In the encapsulated fungal pathogen Cryptococcus neoformans, the P4-ATPase Apt1p is an important regulator of polysaccharide secretion and pathogenesis, but its biochemical characterization is lacking. Phylogenetic analysis revealed that Apt1p belongs to the subclade of P4A-ATPases characterized by the common requirement for a β-subunit. Using heterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 72 publications
1
12
0
Order By: Relevance
“…Human P4-ATPase mutations are linked to neurological disease (ATP8A2, ATP9A, ATP8B2, ATP10B, ATP11A), metabolic and cardiovascular disease (ATP10A, ATP10D), cholestasis and hearing loss (ATP8B1), systemic sclerosis (ATP8B4), severe Covid-19 (ATP11A), cancer progression (ATP11B) and hemolytic anemia (ATP11C) (22,23,(32)(33)(34)(35)(36)(37)(24)(25)(26)(27)(28)(29)(30)(31). The P4-ATPase Apt1-Cdc50 from Cryptococcus neoformans transports a variety of substrates, including GlcCer, and is essential in polysaccharide secretion, stress tolerance, fungal survival inside macrophages, and virulence (38)(39)(40)(41). A Candida albicans drs2∆∆ flippase mutant shows defects in hyphal growth and hypersensitivity to fluconazole (42).…”
Section: Introductionmentioning
confidence: 99%
“…Human P4-ATPase mutations are linked to neurological disease (ATP8A2, ATP9A, ATP8B2, ATP10B, ATP11A), metabolic and cardiovascular disease (ATP10A, ATP10D), cholestasis and hearing loss (ATP8B1), systemic sclerosis (ATP8B4), severe Covid-19 (ATP11A), cancer progression (ATP11B) and hemolytic anemia (ATP11C) (22,23,(32)(33)(34)(35)(36)(37)(24)(25)(26)(27)(28)(29)(30)(31). The P4-ATPase Apt1-Cdc50 from Cryptococcus neoformans transports a variety of substrates, including GlcCer, and is essential in polysaccharide secretion, stress tolerance, fungal survival inside macrophages, and virulence (38)(39)(40)(41). A Candida albicans drs2∆∆ flippase mutant shows defects in hyphal growth and hypersensitivity to fluconazole (42).…”
Section: Introductionmentioning
confidence: 99%
“…Standard PCR reactions were performed with Q5 High-Fidelity DNA Polymerase (NEB, Ipswich, MA, USA). The pESC-URA vector (Agilent Technologies, Santa Clara, CA, USA) digested with BamHI was used as the backbone for APT -containing constructs without CDC50 , while the pESC-URA-APT1-GFP-CDC50-FLAG plasmid [ 19 ] digested with the same enzyme was utilized for CDC50 -containing versions. The APT2 , APT3 , and APT4 sequences were obtained as synthetic cDNA clones from Twist Bioscience (San Francisco, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, Apt1p was recently functionally characterized based on heterologous expression in S. cerevisiae as a lipid transporter with broad substrate specificity. Besides the glycerophospholipids phosphatidylserine (PS), -choline (PC), -ethanolamine (PE), and -glycerol (PG), the transport of galactosyl ceramide (GalCer), glucosyl ceramide (GlcCer), and sphingomyelin (SM) was detected [ 19 ]. Substrate specificity and key features of Apt2-4p remain to be assessed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, mutation studies discovered an essential role of Cryptococcus lipid flippase in echinocandin resistance ( 6 ). The lipid flippase is composed of the core P4 type ATPase (P4-ATPase) and a regulatory subunit Cdc50 ( 7 ). The same study found that fungal mutants with a CDC50 gene of the 250 amino acid exocytoplasmic loop region were highly sensitive to caspofungin.…”
Section: Introductionmentioning
confidence: 99%